KAJIAN SISTEM PERTANIAN TERPADU TANAMAN - SAPI PERAH DI NGANTANG KABUPATEN MALANG - , Rohmad Budiono; , Prof. Dr. Ir. Djoko Prajitno, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this study were: (1) Determine the implementation of an integrated system of agriculture crop - dairy cows and determine the factors that influence the level of integration in integrated farming systems in Ngantang, (2) Find out how much contribution of each crop-livestock farming system and its interaction with total income of farm croplivestock integration, and (3) Determine the factors affecting farm incomes in croplivestock integration. The experiment was conducted in District Ngantang, Malang Regency which include Banjarejo, Sidodadi and Simo-Sidodadi village in April to October 2010. Sampling using stratified random sampling method, collected data were statistically analyzed both descriptive and inference to the qualitative and quantitative data and a hierarchical classification analysis of variance (hierarchical classification) using the program SAS 9.0 (Statistical Analysis System 9.0). The results were: farming is done by Ngantang farming communities have adopted integrated farming system with different levels of integration. Integration pattern of paddy-dairy cattle in low level of integration, integration patterns of potatoes-dairy cattle in medium level of integration and integration patterns of cocoa-dairy cattle in a high level of integration. Each pattern of integration gives a different contribution to total income of farmers. The contribution of rice, potatoes, and cocoa farming are 41.5%, 38.4% and 11.2% of total farm income, respectively. Manure application contributed to the increase in rice production amounted to 1.01 t / ha (increase 17.6%), in potatoes can increase about 5.53 t / ha (increase 53.8%), and in cocoa can increase production about 0.62 t / ha (increase 23.47%), compared with partial manner. The integration in rice-dairy cattle integration gains only on the economic role, while the integration on potato and cocoa-milk dairy cattle cows integration have been obtained advantages in the economic and biology or natural role.